2018
DOI: 10.1080/15226514.2015.1045122
|View full text |Cite
|
Sign up to set email alerts
|

Leucanthemum vulgare lam. crude oil phytoremediation

Abstract: Sites with crude oil pollution have been successfully treated using phytoremediation, but expanding the range of plants that can be used and understanding how exposure impacts the plants are two areas of study that are important to continue. Leucanthemum vulgare has been shown to grow well under a variety of stressful conditions. To examine L. vulgare's ability to both survive crude oil exposure and to reduce crude oil concentrations in soil, plants were placed in soil containing 0, 2.5%, 5%, 7.5% or 10% w/w c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…Similar findings were reported by Sivaram et al ( 2018 ), who compared C3 and C4 plants for the remediation of PAH-polluted soils and stated that the remediation of PAH-polluted soils not only depends on the physicochemical property of PAH but also depends on the nature of the plants and the biologically available concentration of PAH (Reid et al 2000 ; Sivaram et al 2018 ). Our results regarding PAH degradation are in agreement with the assumption of Noori et al ( 2018 ), who documented that the plant roots can facilitate the degradation of pollutants in the soil. They also suggested that PAH degradation could also be the result of plant enzymatic and biochemical activities, as well as the enhancement of microbial community activity in the rhizosphere.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar findings were reported by Sivaram et al ( 2018 ), who compared C3 and C4 plants for the remediation of PAH-polluted soils and stated that the remediation of PAH-polluted soils not only depends on the physicochemical property of PAH but also depends on the nature of the plants and the biologically available concentration of PAH (Reid et al 2000 ; Sivaram et al 2018 ). Our results regarding PAH degradation are in agreement with the assumption of Noori et al ( 2018 ), who documented that the plant roots can facilitate the degradation of pollutants in the soil. They also suggested that PAH degradation could also be the result of plant enzymatic and biochemical activities, as well as the enhancement of microbial community activity in the rhizosphere.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, TPH are considered environmental stressors that can cover the plant root surface and prevent water and nutrient uptake. Moreover, they can enhance the production of reactive oxygen species (ROS), leading to the activation of oxidative stress in plants (Noori et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as plants like other organisms produce ROS in response to abiotic and biotic stresses [55], environmental contamination arising from PH reduce the availability of essential nutrients (like nitrogen and oxygen) required for plant growth [19,56], including water [57] owing to the surface covering of the plant roots by the hydrophobic contaminant, thereby enhancing the production of ROS and hence, oxidative stress in plants [55,58].…”
Section: Induced Chemical Influencementioning
confidence: 99%
“…и остаточным уровнем концентрации нефти в почве. Результаты показали, что L. vulgare может выживать в условиях загрязнения нефтепродуктами и способствовать уменьшению их содержания в субстрате [40]. В Иркутской области T. inodorum распространен в западной и южной частях Среднесибирского плоскогорья и на Южном побережье озера Байкал.…”
Section: результаты и обсуждение подсемейство Asteroidaeunclassified